Reproductive data of a threatened bat, Myotis ruber (E. Geoffroy, 1806) (Chiroptera, Vespertilionidae) in a southern Brazilian deciduous seasonal forest - Bernardi, Itibere P.; Sponchiado, Jonas; Jacomassa, Fabio A. F. [UNESP]; Teixeira, Eli M.; Miranda, Joao M. D.; Passos, Fernando C. (Walter De Gruyter Gmbh, 2014)
Myotis ruber is a widely distributed bat in South America, but it is considered rare and its natural history is virtually unknown. These factors contribute to the classification of the species as vulnerable regionally and near-threatened globally. In this context, the aim of this note is to present new data about the reproductive biology of M. ruber, thus expanding the knowledge about its natural history and, consequently, contributing to the conservation of the species. After an extensive effort to capture bats in southern Brazil, we captured 40 individuals of M. ruber. Pregnant females (n = 17) were observed mainly in October in different years. In addition, seven immature individuals were captured. Based on our results, it is expected that the species will fit the general pattern for bats determined by climate and food resources, but our data do not allow us to assign conclusive reproductive patterns. Although not conclusive, the information presented in this note represents the first opportunity to gather breeding information about this rare and threatened species.
Keywords: Neotropical bat; Red myotis; reproduction; threatened species